Det-WiFi: A Multihop TDMA MAC Implementation for Industrial Deterministic Applications Based on Commodity 802.11 Hardware. (16th April 2017) - Cheng, Yujun; Yang, Dong; Zhou, Huachun
Abstract : Wireless control system for industrial automation has been gaining increasing popularity in recent years thanks to their ease of deployment and the low cost of their components. However, traditional low sample rate industrial wireless sensor networks cannot support high-speed application, while high-speed IEEE 802.11 networks are not designed for real-time application and not able to provide deterministic feature. Thus, in this paper, we propose Det-WiFi, a real-time TDMA MAC implementation for high-speed multihop industrial application. It is able to support high-speed applications and provide deterministic network features since it combines the advantages of high-speed IEEE802.11 physical layer and a software Time Division Multiple Access (TDMA) based MAC layer. We implement Det-WiFi on commercial off-the-shelf hardware and compare the deterministic performance between 802.11s and Det-WiFi under the real industrial environment, which is full of field devices and industrial equipment. We changed the hop number and the packet payload size in each experiment, and all of the results show that Det-WiFi has better deterministic performance.